Active learning surrogate models for the conception of systems with multiple failure modes. (May 2016) - Perrin, G.
Abstract: Due to the performance and certification criteria, complex mechanical systems have to taken into account several constraints, which can be associated with a series of performance functions. Different software are generally used to evaluate such functions, whose computational cost can vary a lot. In conception or reliability analysis, we thus are interested in the identification of the boundaries of the domain where all these constraints are satisfied, at the minimal total computational cost. To this end, the present work proposes an iterative method to maximize the knowledge about these limits while trying to minimize the required number of evaluations of each performance function. This method is based first on Gaussian process surrogate models that are defined on nested sub-spaces, and second, on an original selection criterion that takes into account the computational cost associated with each performance function. After presenting the theoretical basis of this approach, this paper compares its efficiency to alternative methods on an example. Abstract : Highlights: An iterative method to identify the limits of a system is proposed. The method is based on nested Gaussian process surrogate models. A new selection criterion that is adapted to the system case is presented. The interest of the method is illustrated on an analytical example.